My double life : the memoirs of Sarah Bernhardt - Bernhardt, Sarah, 1844-1923 (State University of New York Press, 1999)
My Double Life is the autobiography of the French actress Sarah Bernhardt, who was internationally famed during her lifetime and afterwards as one of the classical theater's all-time greatest stars. Bernhardt's memoirs are composed with a novelist's (or actress's) sense of artistry and suspense that leaves no doubt of the charisma for which she was famed in her "double life," both on- and offstage. Yet at the same time as this book very consciously contributes to the crafting of her image, it also illuminates a whole era: not only the world of theater, but also the worlds of women, politics, society, Europe and America, and, indeed, of history making itself
Keywords: Bernhardt, Sarah, -- 1844-1923.; Bernhardt, Sarah, -- 1844-1923; Actors -- France -- Biography.; Actresses -- France -- Biography.; Actrices -- France -- Biographies.; Acteurs -- France -- Biographies.; Actresses; Actors; France; Biography; Autobiography; autobiographies (literary works); Autobiographies; Biographies; Biographies.; Autobiographies.